Factors associated with shoulder deficit in total rotational motion (DTRM) in adolescent athletes - Mayaly Alves de Oliveira, V.; Rodarti Pitangui, A. C.; Cappato de Araújo, R. (Journal of Human Sport & Exercise, 2020)
Deficit in Total Rotational Motion (DTRM) is a frequent condition in athletes which is directly associated with risk of shoulder injury. However, the identification of risk factors for DTRM in adolescent athletes is not yet established. Thus, the aim of this study was to identify which factors are associated with shoulder deficit in total rotational motion among adolescent athletes. This is an observational cross-sectional study which recruited 178 male adolescent volleyball, handball, swimming, basketball and judo athletes. Information on age, dominance, training frequency, practice time and duration of each session were recorded. The evaluation was composed of a scapular kinematic analysis according to the observational method in order to identify dyskinesis and external and internal rotation amplitude of the glenohumeral joint to assess the presence of internal rotation deficit (GIRD) and DTRM, both using the passive goniometry method. Data analysis was performed using the STATA software in which binary logistic regression was performed with the outcome DTRM and inputting the independent variables of age, training frequency, duration of each session, practice time, modality, scapular dyskinesis and GIRD to identify possible factors. Results shows that adolescent athletes with a weekly training frequency of more than three times a week and affected by GIRD were 2.68 [1.27;5.63] and 9.28 [3.03;28.15] times more likely to present DTRM, respectively. Based on these results, the presence of DTRM was associated with modifiable factors. Physical fitness strategies are advisable in order to control such factors and prevent injuries associated with DTRM.